DOKTRIN POLITIK SYI'AH IMAMIYAH DALAM DIMENSI FILSAFAT HUMANISME PRAGMATIS WILLIAM JAMES - , Eva Linta Cahyani; , Prof. Dr. Syamsul Hadi, SU., MA., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study reviews the Shi'a Imami political doctrine. This observation departs from the background of the symptoms of dehumanization as a form of humanitarian crisis raises issues that need to be outlined. Symptoms of dehumanization in question is the negative consequences that arise from the application of the Shi'a Imami political doctrine. The Shiâa Imami political doctrine in this study dissected through analysis of William James pragmatic humanism philosophy in the context of: (a) universal awareness reflected in the consciousness of the cosmic evolutionary process that is constantly changing and demanding humans adapt to all its potential, (b) concept of the creation of man as a being versatile dimension to the ownership aspect of autonomy freedom, responsibilities, and limitations to make people think rationally, critically, and ethically, (c) the enligthen of spiritual and intellectual mental to realize the ideal life. From the whole process of research conducted it was concluded that: (a) the truth of the Shi'a Imami political doctrine is doubtful because the doctrine is not divine, but a mere human science products metamorphosed to the certain conditions and interests, (b) the political doctrine is problematic and difficult to be justified logically and scientifically, so it cant provide a scientific satisfaction for its adherents, (c) the political doctrine contains elements of discrimination by differentiating the right, the ability, and the responsibility of the Shiâa people in creating the ideal life, (d) the doctrine depriving the Shiâa peopleâs freedom of right by believing the binding and determinants doctrine. From some of these previous conclusions, a result of the alleged dehumanisation in Shiâa Imami political doctrine applying proven and absolutist truth claims of Shiâa Imami political doctrine can not be justified.